Rapid diagnosis and identification by PCR of Yersinia ruckeri isolated of Oncorhynchus mykiss from Canta, Lima, Peru - Sirvas-Cornejo, Susana (2011)
Twenty individuals of rainbow trout were sampled (fry and juveniles) from Acochinchan Fishfarm (Canta, Lima - Peru), and analyzed with the Polimerase Chain Reaction test (PCR ) in order to achieve a rapid identification of Yersinia ruckeri, which is the pathogen agent that causes the enteric red mouth disease (ERM) and produces high rates of mortality. Nine fish samples were asymptomatic, while 11 of them showed signs of ERM. In addition, 22 bacterial strains were isolated from the liver, spleen and kidney. PCR and specific primers (16S rRNA), were used to amplified a specific 575 bp DNA fragment of Yersinia ruckeri. Nineteen strains were identified as Yersinia ruckeri by PCR in symptomatic and asymptomatic fishes. It was established a diagnosis time of 26 hours, compared with the 2 or 3 days that would take the diagnosis using biochemical tests.